Behavior of Concrete Beams encasing castellated Steel Sections with Different Opening Shapes - Qasim, Mohammed A.; Waryosh, Waleed A. (Engineering, Technology & Applied Science Research, 2025)
This study investigates the behavior of concrete-encased castellated steel beams featuring various aperture geometries and shear stud connector configurations. Five Composite Castellated Beam (CCB) specimens were tested under two-point loading conditions, including one control specimen with a solid steel section and four specimens with castellated steel beams encased in Normal-Strength Concrete (NSC). The castellated beams featured either Hexagonal (H) or Rectangular (R) openings, and the shear stud connectors provided either Full (F) or Partial (P) interaction between the steel and concrete components. The research objectives were to determine the maximum load capacity for each sample under applied loads, analyze the resulting deformations, and assess the impact of the opening shape and shear connections on the beam performance. The results showed that the H opening improved the load-bearing capacity by 19% and reduced the deflection and horizontal displacement by 21.47% and 12.86%, respectively, compared to the R opening sample. Specimens with F interaction exhibited a higher load capacity and lower deflection and horizontal displacement than those with P interaction. The F configuration increased load tolerance by 2.44% and decreased the deflection and horizontal displacement rates by 4.17% and 5.86%, respectively, relative to the P configuration. The findings demonstrate the influence of aperture geometry and shear connections on the structural performance of concrete-encased castellated steel beams, providing insights for optimizing their design in composite construction.